The monetary policy implications of behavioral asset bubbles - Rhys ap Gwilym (Cardiff University, Cardiff Business School, 2009)
I introduce behavioral asset pricing rules into a wider dynamic stochastic general equilibrium framework. Asset price bubbles emerge endogenously within the model. I find that in this model the only monetary policy that would be likely to enhance welfare is a counter-intuitive running with the wind policy. I conclude that the optimal policy is highly dependent on the nature of the behavioral rules that are stipulated. Given that monetary authorities have limited information about the ways in which agents actually behave, a systematic monetary policy response to asset price misalignments is unlikely to enhance welfare.
Keywords: 330; Verhaltensökonomik; Kapitalanlage; Bubbles; Geldpolitik